2020
DOI: 10.35508/jhbs.v2i4.2827
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control with Social Media Addiction in Students of SMA Negeri 3 Kota Kupang

Abstract: Social media addiction can be seen as a form of internet addiction, in which individuals show an urge to use social media excessively. A person's inability to control himself to connect to the internet is the cause of internet addiction. The purpose of this study was to determine the relationship between self-control and social media addiction in students of SMA Negeri 3 Kota Kupang. The sampling technique used convenience sampling with a total sample size of 117 subjects. The analysis in this study used non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Sagar (2021), in his study with university students in Turkey, indicated the effect of self-control on social media addiction. Similarly, Bheo et al, (2020) found a negative relationship between self-control and social media addiction in the high school sample. Additionally, social media addiction negatively affects the mental health of emerging adults (Shensa et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Sagar (2021), in his study with university students in Turkey, indicated the effect of self-control on social media addiction. Similarly, Bheo et al, (2020) found a negative relationship between self-control and social media addiction in the high school sample. Additionally, social media addiction negatively affects the mental health of emerging adults (Shensa et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…In other words, the results revealed that emerging adults with poor self-control are more likely to have higher FoMO, which in turn increases social media addiction, and ultimately leads to a greater risk of distress. Although the studies in the existing literature have examined the relationship between these variables (Bheo et al, 2020; Elhai et al, 2016; Germano & Brenlla, 2021), a theoretical model in which all these variables are considered together has not been presented. In addition to the previous hypothesis in the model, a positive effect of FoMO on social media addiction was observed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chaplin (2006), self-control is the capacity to direct one's own behavior and prevent impulsive behavior. According to the findings of a study conducted by Bheo, Lerik, and Wijaya (2020) on 117 students, of which 80 participated and 37 had an addiction, the majority of students do not have a high level of addiction to social media.…”
Section: Self-control At Sma Negeri 5 Padangmentioning
confidence: 99%